New leash on life (Dogfather, 2,, 2017)
"When former attorney and current dog whisperer Shane Kilcannon messes up his chance with a beautiful stranger whose confident smile and quick wit intrigue him more than any other woman he's ever met, he's ready to snarl like one of his beloved pit bulls. But Shane's work with the wildest and wariest of his family's rescue dogs has taught him patience and persistence. When his father hands him the opportunity to work alongside that very same woman who has come to town with ground-breaking tourism plans, he seizes it..."--Page 4 of cover.

Sit... stay... beg (Dogfather, Bk. 1,, 2017)
Garrett Kilcannon, a former dot com super-success who now devotes his life to rescuing dogs and finding them homes, prefers to keep his secrets buried as deep as a dog hides his bone. So when Garrett's father pressures him to be interviewed for an in-depth profile, he doesn't care that the journalist is a childhood friend or drop dead gorgeous. He has zero tolerance for the media until he sees a different side of the woman when she gets through the walls of a depressed recuse dog. Unwillingly charmed and undeniably attracted, Garrett agrees to the interview that could break down a few of his emotional walls, too..."-Page 4 of cover.

Bad to the bone (The Dogfather, 5,, 2018)
"After fourteen years in prison, Trace Bancroft heads back to Bitter Bark with his mutt, Meatball, and runs into Daniel Kilcannon, who offers to provide some medical care for the dog. Trace knows that would mean seeing Molly Kilcannon, a girl who shared one crazy night with him before his life took a turn for the worst. But when Meatball's illness intensifies, Trace has to face Molly again, and pray she'll save his dog, no matter what their history. When Trace Bancroft arrives at Waterford Farm with a critically ill dog, Molly Kilcannon;s world is shaken to the core. Firmly believing Trace died in a bar fight years ago, Molly never told anyone that the bad boy of Bitter Bark was the father of Prudence Kilcannon, her very good thirteen year old daughter. But Molly has promised to tell Pru the truth about her conception, and now that truth is a living breathing ex-con whose very existence could change everything, including a precious mother-daughter relationship."

Bark! the herald angels sing (Dogfather, 8,, 2018)
With Christmas and a holiday wedding fast approaching, there's happy chaos in the air at Waterford Farm. However, not everyone in the Kilcannon clan is caught up in the magic of the moment. Matriarch, octogenarian, and beloved blogger Gramma Finnie hears the clock of her long life ticking far to fast, while her great-granddaughter, teenager Pru, feels squeezed out of planning her mother's nuptials. But when this unlikely duo is tasked with the project of producing the "somethings" for the wedding and only have Christmas Eve to get the job done-Gramma Finnie and Pru have a purpose and a plan. They set off to find the perfect old, new and blue treasures, but it doesn't take long for things to spin out of control faster than Gramma's Toyota in a snowstorm. Detoured by a stray border collie, thwarted by nature and an elf parade, and trapped by a rifle-toting mountain man, it will take more than the power of the Kilcannon clan to save these two from a Christmas catastrophe. It will take the luck of the Irish, a love story from long ago, and a whole lot of help from the angels to make this holiday merry and bright.

Double dog dare (Dogfather, 7,, 2018)
The Dogfather has one more child to marry off, but Darcy Kilcannon has no interest in her father's matchmaking shenanigans. The youngest Kilcannon is not looking for a husband. Darcy is ready to launch her own business in town, move into her own apartment, and become her own woman. But when she walks into the gorgeous brownstone that her father just "happened" to help her find, Darcy takes one look at the hot landlord and she knows the Dogfather has been up to his old tricks. Sure the landlord's a hunk and a half, but his "no pets" policy is a huge turnoff to a dog groomer who won't dream of living without her beloved Kookie. Joshua Ranier moved to Bitter Bark to get out of the shadow of his overbearing stepfamily and keep his shattered heart securely on ice. His only focus is his construction business, and the brownstone he's renting and renovating, until he meets the sexy, sassy blonde tenant sneaking a fuzzy white dog even though he's banned pets because of construction dangers. Then Josh starts thinking about things he shouldn't. And it isn't when the rent's due. But when a blind dog lands on Josh's doorstep, he needs Darcy's help. As they race to restore little Stella's vision and solve a mystery that's tearing his family apart, Josh and Darcy begin to see the light, too. It will take one double dog dare, two precious puppers, and the full power of the Kilcannon clan for this couple to find their happy ever after.

Old dog new tricks (Dogfather, 9,, 2019)
Daniel Kilcannon, the veterinarian known as the Dogfather, has been widowed for four years. He's spent the time running the largest canine rescue and training facility in North Carolina and pulling some strings to make sure each of his six grown children find a love like the one he lost when his beloved Annie dies. But as the years slip by, Daniel's decision to never love again is starting to make him restless. When a woman who was pivotal to his past arrives in Bitter Bark, he wonders if her appearance is coincidence or the guiding hand of his dearly departed wife....but the truth is neither. She's about to change his life again in ways he could never have imagined. And Daniel isn't sure if his hear or his family will ever recover from the impact.